Analysis of Humans Cruelty in Kari Sutherland's "Dumbo Circus of Dreams" - Mamluatur Rahmah; Erika Citra Sari Hartanto (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This article deals with environmental issues represented in the Dumbo Circus of Dreams novel by Kari Sutherland. There are some environmental issues which are represented clearly in The Dumbo Circus of Dreams novel. There are three problems to discuss in this article. The first is about how elephants are treated badly by humans. The second is about the impact of human cruelty towards elephants. The last is about the role of humans in restoring animals rights. Descriptive qualitative method is used by applying Garrad’s theory of ecocriticism to analyze the problems. The results of this article are: the elephants treated by humans as moneymakers, physical abuse, and verbal abuse. It also found that the impact of human cruelty towards elephants includes limited life and physical and mental injuries. The role of humans in restoring animal rights through human awareness of animal rights and replacing animals with other objects. Keywords: Animals, Ecocriticism, Human Awareness, Human Cruelty, Impact.